Perbincangan Sosialisasi Kebijakan Pendidikan Islam - Dian Namora; Abu Bakar (Al Hikmah: Journal of Education, 2021)
The purpose of writing this article is to examine the approach to the formulation of education policy problems, the stages of policy formulation and the formulation of education policies, actors in the formulation of education policies and must be able to socialize education policies and education policy socialization strategies through the socialization media of education policy. This method of writing uses the methodology of the study of literature. The writing of this article is done by reviewing several journals related to education policy contained in the google scholar data base. The results of the study are then spelled out through scientific articles. To complete the Discussion of Socialization of Islamic Education Policy, education organizers must be able to know the framework of education policy development. Namely by contributing and approaching the formulation of education policy problems, the stage of formulation of policy problems and the formulation of education policies, actors in the formulation of education policies and must be able to do the stage of socialization of education policy at the preparatory stage, the stage of mimicking (play stage), and the stage of action (game stage), and able to conduct educational policy socialization strategies through the medium of socialization of policy.  education.Tujuan penulisan artikel ini adalah untuk mengkaji pendekatan terhadap perumusan masalah kebijakan pendidikan, tahapan perumusan masalah kebijakan dan perumusan kebijakan pendidikan, aktor dalam perumusan kebijakan pendidikan serta harus mampu melakukan sosialisasi kebijakan pendidikan dan strategi sosialisasi kebijakan pendidikan melalui media sosialisasai kebijakan pendidikan. Metode penulisan ini menggunakan metodologi studi kepustakan. Penulisan artikel ini dilakukan dengan mengkaji beberapa journal yang berhubungan dengan kebijakan pendidikan yang terdapat pada data base google scholar. Hasil dari pengkajian kemudian dijabarkan melalui artikel ilmiah. Untuk menyelesaikan Perbincangan Sosialisasi Kebijakan Pendidikan Islam maka penyelenggara pendidikan harus mampu mengetahui kerangka kerja pengembangan kebijakan pendidikan. Yaitu dengan mengkontribusikan dan melakukan pendekatan terhadap perumusan masalah kebijakan pendidikan, tahapan perumusan masalah kebijakan dan perumusan kebijakan pendidikan, aktor dalam perumusan kebijakan pendidikan serta harus mampu melakukan tahapan sosialisasi kebijakan pendidikan pada tahap persiapan (preparatory stage), tahap meniru (play stage), dan tahap tindakan (game stage), serta mampu melakukan strategi sosialisasi kebijakan pendidikan melalui media sosialisasai kebijakan pendidikan.